Molecular Mechanisms Linking Empagliflozin to Renal Protection in the LLC-PK1 Model of Diabetic Nephropathy - Vjera Mihaljević; Milorad Zjalić; Tomislav Kizivat; Tea Omanović Kolarić; Martina Smolić; Edi Rođak; Marina Čović; Lucija Kuna; Robert Smolić; Aleksandar Včev; Ines Bilić Ćurčić (Biomedicines, 2022)
Aims: Chronic diabetes complications, including diabetic nephropathy (DN), frequently result in end-stage renal failure. This study investigated empagliflozin (SGLT2i) effects on collagen synthesis, oxidative stress, cell survival, and protein expression in an LLC-PK1 model of DN. Methods: Combinations of high glucose (HG) and increasing empagliflozin concentrations (100 nM and 500 nM), as well as combinations of HG, H2O2, and empagliflozin, were used for cell culture treatment. The cell viability, glutathione (tGSH), ECM expression, and TGF-β1 concentration were measured. In addition, the protein expression of Akt, pAkt, GSK3, pGSK3, pSTAT3, and SMAD7 was determined. Results: The addition of both concentrations of empagliflozin to cells previously exposed to glucose and oxidative stress generally improved cell viability and increased GSH levels (p < 0.001, p < 0.05). In HG30/H2O2/Empa500-treated cells, significant increase in pSTAT3, pGSK3β, GSK3β, SMAD7, and pAKT levels (p < 0.001, p < 0.001, p < 0.05) was observed except for AKT. Lower drug concentrations did not affect the protein expression levels. Furthermore, empagliflozin treatment (100 nM and 500 nM) of HG30/H2O2-injured cells led to a decrease in TGF-β1 levels (p < 0.001). In cells exposed to oxidative stress and hyperglycemia, collagen production remained unchanged. Conclusion: Renoprotective effects of empagliflozin, in this LLC-PK1 cell model of DN, are mediated via activation of the Akt/GSK-3 signalling pathway, thus reducing oxidative stress-induced damage, as well as enhanced SMAD7 expression leading to downregulation of TGF-β1, one of the key mediators of inflammation and fibrosis.